Analisis Preferensi Konsumen pada Jasa Perawatan Sepatu di Surabaya - Faris Fepriyanto; Helena Sidharta (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2025)
The growth of the footwear industry in Indonesia, particularly in the city of Surabaya, presents significant opportunities for shoe care services. This study aims to analyze consumer preferences toward shoe care services in Surabaya by considering four key attributes: reputation, desired results, severity level of shoe condition, and location. This research employs a quantitative method with a conjoint analysis approach and is processed using SPSS 27 software. Data were collected through a questionnaire distributed to 384 respondents who had previously used shoe care services. To generate representative attribute combinations, the orthogonal array method was used, resulting in nine optimal stimuli to assess consumer preferences. Based on the importance values, the most influential attribute in consumer decision-making is the desired result, followed by severity level, reputation, and location. The most preferred combination among respondents includes services recommended by close acquaintances, effective stain removal results, the ability to handle shoes with moderate damage, and a conveniently accessible location. These findings provide strategic insights for shoe care service providers to develop offerings that align with market preferences and enhance competitiveness amid the growing number of similar businesses in Surabaya.